Modulation of experimental acute lung injury by exosomal miR-7704 from mesenchymal stromal cells acts through M2 macrophage polarization - Wei-Ting Lin; Hao-Hsiang Wu; Chien-Wei Lee; Yu-Fan Chen; Lawrence Huang; Jennifer Hui-Chun Ho; Oscar Kuang-Sheng Lee (Molecular Therapy: Nucleic Acids, 2024)
Acute lung injury (ALI) is a life-threatening condition with limited treatment options. The pathogenesis of ALI involves macrophage-mediated disruption and subsequent repair of the alveolar barriers, which ultimately results in lung damage and regeneration, highlighting the pivotal role of macrophage polarization in ALI. Although exosomes derived from mesenchymal stromal cells have been established as influential modulators of macrophage polarization, the specific role of exosomal microRNAs (miRNAs) remains underexplored. This study aimed to elucidate the role of specific exosomal miRNAs in driving macrophage polarization, thereby providing a reference for developing novel therapeutic interventions for ALI. We found that miR-7704 is the most abundant and efficacious miRNA for promoting the switch to the M2 phenotype in macrophages. Mechanistically, we determined that miR-7704 stimulates M2 polarization by inhibiting the MyD88/STAT1 signaling pathway. Notably, intra-tracheal delivery of miR-7704 alone in a lipopolysaccharide-induced murine ALI model significantly drove M2 polarization in lung macrophages and remarkably restored pulmonary function, thus increasing survival. Our findings highlight miR-7704 as a valuable tool for treating ALI by driving the beneficial M2 polarization of macrophages. Our findings pave the way for deeper exploration into the therapeutic potential of exosomal miRNAs in inflammatory lung diseases.